A study of occupational stress among professional college teachers - Thekedam , Joseph Sebastian (Gyan Management Journal, 2011)
Employees in all sectors experience one form of stress or another at their workplaces. Teaching is traditionally considered to be one of the most stressful occupations. The difficulties that teachers face in their effort to respond to their continuously altered and varied roles constitute a critical issue that the academic community should pay special attention to and explore on a systematic basis. The aim of the present study was to investigate the main aspects of stress among professional college teachers and the different coping strategies that they use to alleviate their stressors. Qualitative as well as quantitative data were collected by means of semi-structured interviews with teachers and questionnaires that were administered to 281 teachers. Each participant received a survey questionnaire consisting of three sections. Sections I and II were used to gather data pertaining to the sources of occupational stressors and the coping strategies used by the participants. Section III was designed to request information concerning personal and professional demographic characteristics of each research participant. An analysis of the data was completed on all three sections. Based on the findings of the study, recommendations are included to utilize effective coping strategies to reduce the negative effects of their stress.
Keywords: Stress; Stressors; Coping Strategies; Burnout; Professional College Faculty